Między słowem oryginału a lekturą tłumacza - Kardyni-Pelikanová, Krystyna (Slavia Occidentalis, 2011)
The text deals with the translatological problem which treats translation as one of the main testimonies of the reception of literary texts in a foreign culture. The author is interested in: reconstruction of a specific model of reading Polish literary works by the selected Czech translator, finding the reasons why this specific model is applied as well as reconstruction of the results of all such efforts. The subject of the analysis is the translational work of the Czech poet and eminent translator – Vladimír Holan.